Conquering Imposter Syndrome - Lynne Lambdin (Journal of New Librarianship, 2024)
Imposter Syndrome is an experience that many new professionals struggle with in their day-to-day work lives. With a strong technological background, succeeding in a systems librarian role seems natural and easy. However, some responsibilities require more traditional skills associated with librarianship, like reference services, instructional support, and collection management. This column emphasizes the significance of professional development and the necessity in gaining a skill set that ensures a more well-rounded library professional and library employee. It offers a head-on approach to combating the feeling of inadequacy when changing one’s career. Imposter syndrome does not have to be a long-term feeling.